L-ASPARAGINASE-INDUCED DIABETIC KETOACIDOSIS IN AN ADULT WITH ACUTE LYMPHOBOLASTIC LEUKEMIA - Gargar, Jenn Danielle; Lat, Karen Loise; Tan, Henny Tannady; Dela Fuentes Rosales, Reynaldo (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The mainstay treatment for acute lymphoblastic leukemia (ALL) includes L-asparaginase, doxorubicin, vincristine, and prednisone. Hyperglycemia is common with asparaginase, with or without glucocorticoid therapy. Development of diabetic ketoacidosis (DKA) however, is rare and mostly reported in children with an incidence of 0.8%. Incidence among adults is unknown. Fourteen cases have been reported in patients below 18 years old, and only 3 occurring in 21 to 25-year-olds. This case is of a 57-yearold female with precursor B cell ALL developing DKA post 3rd cycle of L-asparaginase therapy. CASE Literature reviewed from 1986 to present revealed seventeen cases of DKA post L-asparaginase therapy. CONCLUSION This report shows that DKA from L-asparaginase occurs even in the older population. It is vital that patients with hyperglycemia and decreased sensorium receiving L-asparaginase for ALL be screened for DKA. Determination of risk factors among patients who develop DKA from L-asparaginase is important in order to prevent future incidences.